METODE KALIBRASI RADAR TRANSPONDER ROKET MENGGUNAKAN DATA GPS (CALIBRATION METHOD OF RADAR TRANSPONDER FOR ROCKET USING GPS DATA) - Widada, Wahyu (Indonesian Journal of Aerospace, 2012)
This paper discusses the method of calibration of radar transponders for the rocket launch applications using GPS data. Calibration is performed by measuring the distance of two positions with GPS data and used as a reference for the calibration range radar transponder. Transponder is placed on the measured position and the radar transceiver is placed in a position of radar base station. The obtained results shows that the calibration method is very easy to do, reference to a longer distance can improve the accuracy result of the calibration. We obtained a calibration factor value for the radar system used in the experiment is 0.9275..Keywords: Radar transponder, GPS, Google-earth, Calibration method